Detection of oligoclonal IgG kappa and IgG lambda bands in cerebrospinal fluid and serum with Hevylite™ antibodies. comparison with the free light chain oligoclonal pattern - Zeman, David; Hradílek, Pavel; Svagera, Zdeněk; Mojžíšková, Eva; Woznicová, Ivana; Zapletalová, Olga (Fluids and barriers of the CNS, 2012)
BACKGROUND: Oligoclonal IgG bands in cerebrospinal fluid that are absent in serum indicate intrathecal IgG synthesis and are a sensitive marker of CNS inflammatory diseases, in particular multiple sclerosis. It may be of interest to determine whether these bands are predominantly IgGκ or IgGλ. METHODS: We have used Hevylite™ antibodies and developed a technique for detection of oligoclonal IgGκ and IgGλ bands by means of isoelectric focusing followed by immunoblotting. The same technique was used for oligoclonal free κ and free λ detection. Among several techniques tested, affinity immunoblotting appears to be the most sensitive; it can detect less than 1 ng of IgGκ or IgGλ paraprotein. We compared oligoclonal IgG profiles with those of oligoclonal IgGκ and IgGλ. There was good agreement concerning the presence or absence of intrathecal synthesis. We observed the ratios between oligoclonal IgGκ and IgGλ bands, and they did not always match the ratios between free κ and free λ bands. We were also able to detect antigen-specific CSF-restricted oligoclonal IgGκ and IgGλ bands in neuroborreliosis. It remains to be determined subsequently by a clinically-oriented prospective study, whether predominant IgGκ/IgGλ or free κ/free λ can be observed more frequently in particular diseases with oligoclonal IgG synthesis. DISCUSSION: Very sensitive detection of oligoclonal IgGκ and IgGλ bands in cerebrospinal fluid with Hevylite antibodies is feasible; detection of antigen-specific IgGκ or IgGλ is possible as well. In particular situations, e.g. when difficulties arise in distinguishing between oligoclonal and monoclonal pattern, the test may be of considerable clinical value.